Norms and Values in UK Science Engagement Practice. Issue 1 (2nd January 2016) - Jensen, Eric; Holliman, Richard
Abstract : In recent years, there has been a rhetorical shift from 'deficit' to 'dialogue' and 'engagement' in UK policy and institutional discourse about science communication. Past efforts to reduce public scientific literacy deficits have been overshadowed by calls for dialogue between scientists, science communicators and non-scientists. However, it is unclear how this rhetorical shift has translated into a real change in the guiding principles and practices of UK science engagement. This study investigates reported practices and discourse of UK science engagement practitioners from a variety of professional backgrounds. Quantitative and qualitative data were gathered using questionnaires and focus groups. The analysis employed a theoretical lens informed by Bourdieu's theory of practice, Irwin's taxonomy of first (deficit), second (dialogue) and third (contextual) 'orders' of engagement and theoretical conceptualizations of social change from cultural psychology and sociology. Results suggest that participating practitioners' reported experience was predominately first order, although current definitions and discussions of engagement by a small number of practitioners indicate some limited acceptance of dialogue-oriented thinking. Such potential movement from past practice to current thinking is highly contingent however, not least because so few practitioners had experienced second- or third-order engagement. The implications of these findings are explored both in terms of understanding patterns in UK science engagement and what they portend for Bourdieu's theory of practice and social change.